Self-reported non-communicable diseases and associated socio-demographic status among ethnic minority populations in Vietnam, 2019. Issue 2 (September 2020) - Van Minh, Hoang; Long, Khuong Quynh; Ha, Nguyen Thanh; Duong, Doan Thi Thuy; Trung, Tran; Huong, Hoang Thi; Van Huan, Nguyen; Hanh, Tran Thi Tuyet; Lan, Vu Thi Hoang; Huong, Nguyen Mai; Oanh, Luu Thi Kim; Trang, Nguyen Thi Thu; et al.
The aim of this study was to report the prevalence of self-reported non-communicable diseases among ethnic minority populations in Vietnam and related factors. A total of 5033 individuals aged 15 years and older who belonged to ethnic minority populations from 12 provinces in Vietnam completed a household survey. The overall prevalence of self-reported non-communicable diseases was 12.4% (95% CI: 11.5%–13.4%). Cardiovascular diseases were the most prevalent, followed by diabetes. Ethnicity was shown to have an independently significant correlation to having any non-communicable diseases. Older people, near-poor and non-poor people had significantly higher odds of having non-communicable diseases as compared to younger and poor people.